Mitigasi Bencana Non Alam Berbasis Masyarakat Saat Dan Pasca Pandemi Covid_19 Di Kabupaten Karawang - Salman Salman; Indah Laily Hilmi; Gun Gun Gumilar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This research aims as an effort to increase public knowledge and awareness through socialization and health education about steps to prevent transmission of covid_19, understanding the importance of Clean and Healthy Living (PHBS) behavior, Healthy Living Community Movement (GERMAS) which can be used as behavior patterns in the future. pandemic Covid_19. In addition, efforts to empower and increase community participation in the use of traditional medicinal plants found in the surrounding environment as health ingredients. This service method is carried out in 2 stages, the first stage is carrying out health education which aims to increase knowledge, awareness, encouragement and motivation to the community to maintain health and always adhere to the application of health protocols in every activity carried out, while the second stage is carried out with training making health potions by utilizing traditional medicinal plants for health maintenance, disease prevention and health care that can be done during and after the Covid_19 pandemic. The results of the study showed that the socialization and health education carried out had a positive impact on increasing public knowledge. Increased knowledge will have an impact on behavior, especially behaviors that can prevent disease, and increase body resistance during the Covid-19 pandemic carried out by, from and for the community itself as an effort to mitigate community-based non-natural disasters.